Psychomotor control in a virtual laparoscopic surgery training environment: gaze control parameters differentiate novices from experts - Wilson, Mark (Springer-Verlag, 2010)
BACKGROUND: Surgical simulation is increasingly used to facilitate the adoption of technical skills during surgical training. This study sought to determine if gaze control parameters could differentiate between the visual control of experienced and novice operators performing an eye-hand coordination task on a virtual reality laparoscopic surgical simulator (LAP Mentor™). Typically adopted hand movement metrics reflect only one half of the eye-hand coordination relationship; therefore, little is known about how hand movements are guided and controlled by vision. METHODS: A total of 14 right-handed surgeons were categorised as being either experienced (having led more than 70 laparoscopic procedures) or novice (having performed fewer than 10 procedures) operators. The eight experienced and six novice surgeons completed the eye-hand coordination task from the LAP Mentor basic skills package while wearing a gaze registration system. A variety of performance, movement, and gaze parameters were recorded and compared between groups. RESULTS: The experienced surgeons completed the task significantly more quickly than the novices, but only the economy of movement of the left tool differentiated skill level from the LAP Mentor parameters. Gaze analyses revealed that experienced surgeons spent significantly more time fixating the target locations than novices, who split their time between focusing on the targets and tracking the tools. CONCLUSION: The findings of the study provide support for the utility of assessing strategic gaze behaviour to better understand the way in which surgeons utilise visual information to plan and control tool movements in a virtual reality laparoscopic environment. It is hoped that by better understanding the limitations of the psychomotor system, effective gaze training programs may be developed.